2004
DOI: 10.1021/nl048758u
|View full text |Cite
|
Sign up to set email alerts
|

Magnetite (Fe3O4) Core−Shell Nanowires:  Synthesis and Magnetoresistance

Abstract: High quality MgO/Fe 3 O 4 core−shell nanowires have been successfully synthesized by depositing an epitaxial shell of Fe 3 O 4 onto single crystal MgO nanowires. The material composition and stoichoimetric ratio have been carefully examined and confirmed with a variety of characterization techniques. These novel structures have rendered unique opportunities to investigate the transport behavior and spintronic property of Fe 3 O 4 in its one-dimensional form. Room-temperature magnetoresistance of ∼1.2% was obse… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

14
201
0

Year Published

2005
2005
2015
2015

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 331 publications
(215 citation statements)
references
References 28 publications
14
201
0
Order By: Relevance
“…The circles represent resistance (R) data points acquired from original I-V scans and the line represents best fit. Electrical resistance of single Fe 3 O 4 nanowire at room temperature is around 5 Â 10 À4 X m, which is comparable to epitaxial thin films 14,25 and higher than bulk single crystal Fe 3 O 4 . 26 Electrical resistance below 120 K is almost 2 orders of magnitude higher compared to room temperature.…”
mentioning
confidence: 85%
See 2 more Smart Citations
“…The circles represent resistance (R) data points acquired from original I-V scans and the line represents best fit. Electrical resistance of single Fe 3 O 4 nanowire at room temperature is around 5 Â 10 À4 X m, which is comparable to epitaxial thin films 14,25 and higher than bulk single crystal Fe 3 O 4 . 26 Electrical resistance below 120 K is almost 2 orders of magnitude higher compared to room temperature.…”
mentioning
confidence: 85%
“…Epitaxially grown MgO/Fe 3 O 4 core shell nanostructures were found to have 1.2% MR at room temperature under 1.8 T applied field, which is credited to the tunneling of spin-polarized electrons across the antiphase boundaries. 14 Terrier et al measured the transport properties of several polycrystalline nanowires and reported 8.5% MR at room temperature and did not observe any anisotropy. 15 The magneto-electron transport properties of an individual single crystalline Fe 3 O 4 nanowire are still inconsistent.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…[1][2][3][4][5] Multifunctional magnetic nanowires (metal or oxide) have received much attention due to their potential application in perpendicular data recording, spintronics devices, scanning tips in magnetic force microscope, and in other biological applications. [6][7][8][9][10][11] Among them, magnetite (Fe 3 O 4 ) have garnered much consideration for magnetoresistance 12,13 and spin filter device applications. 14 Magnetite has been the subject of extensive research efforts because of high spin polarization and above room temperature Curie temperature, which finds applications in magneto-electronics.…”
mentioning
confidence: 99%
“…A room temperature ferromagnet with 858 K curie temperature and 100% spin polarization at the Fermi level with majority spin electrons exhibiting insulating or semiconducting behavior while the minority spins showing the metallic behavior has rendered the Fe 3 O 4 to be obvious choice for magneto-electronics. 15 Spin polarization or magneto-electronic measurements on Fe 3 O 4 were probed through electrical contacts to the oxide via evaporated metal electrodes, 12 or via spin-polarized electron spectroscopy, 16 or electron holography. 17 Magnitude of the spin polarized current was found to depend on material microstructure, grain size, grain boundary, defects, strain effects, and surface/interface reconstruction.…”
mentioning
confidence: 99%